Teaching Grammar for the TOEIC Test: Is Test Preparation Instruction effective? - Nishitani, Atsuko (Glottodidactica, 2006)
This study was conducted to investigate the effect of test preparation instruction on TOEIC (Test of English for International Communication) scores, especially on the grammar section. Data were gathered in two intact classes, a TOEIC preparation class and a communicative grammar class, at a Japanese university during two semesters (Spring 2004 and Spring 2005). A pretest and a posttest were administered on the first day and the last day of class respectively, and the means were compared. The results showed that the students in the TOEIC preparation classes demonstrated statistically significant score gains. The findings of this study suggest that test preparation instruction is effective in improving scores of the grammar section of the TOEIC test.